Plane symmetric bulk viscous domain wall in Lyra geometry - Pradhan,Anirudh (2007)
In this paper general solutions are found for domain walls in Lyra geometry in the plane symmetric spacetime metric given by Taub. Expressions for the energy density and pressure of domain walls are derived in both cases of uniform and time varying displacement field beta. Some physical consequences of the models are also given. Finally, the geodesic equations and acceleration of the test particle are discussed.